Analiza načrtovanega kurikula za vrtce na področju glasbene vzgoje - Denac, Olga (Sodobna pedagogika, 2007)
Issues concerning the planning of music education are connected with the philosophical dimension of the development of music curricula and are especially topical in connection with the introduction of the Kindergarten Curriculum (1999), bringing novelties at the system and contents levels. Therefore, the systematic monitoring and determination of the quality of the planned curriculum is indispensable for a successful education process in the music field. The article presents the results of the first and second stages of research in which we included 159 kindergarten teachers from all of Slovenia. The purpose of the research was to determine the place and role of music education in the planned kindergarten curriculum and to identify any problems encountered by kindergarten teachers in the implementation of individual principles of the curriculum as part of the operative planning of music education. We analysed the planned curriculum in terms of structure, activities, goals, principles, contents, methods and means of work. The results of the research show that music education in the field of art is losing its professional autonomy and that in the planning of the music education process kindergarten teachers are only partially implementing individual curriculum principles.
Keywords: predšolska vzgoja; kurikulum; curriculum; glasbena vzgoja